The Effect of Immediate Obturator Reconstruction after Radical Maxillary Resections on Speech and other Functions - Mehmet Dalkiz; Ahmed Suat Dalkiz (MDPI AG, 2018)
Objective: Maxillectomy often results in a high level of morbidity with significant psychological and functional implications for patients. The aims of the present study were to assess the effectiveness of the maxillary obturator as a speech rehabilitation aid, to examine the influence of dentition on speech intelligibility, to restore patients’ regular daily activity as soon as possible, and to maintain patients’ psychological well-being throughout the treatment. Patients and Methods: Forty-one palatomaxillary immediate obturator and definitive reconstruction patient treatments were reviewed at a clinic (Ankara, Turkey). Patients aged between 20 and 73 years with surgically acquired partial maxillary defects were included in this study. All patients were rehabilitated with immediate and definitive obturators. The patients were given immediate surgical obturators which were adjusted to the defect area with a tissue conditioner. By employing this procedure and relining with the tissue conditioner weekly, immediate obturators were used in the interim stage of the treatment. As interim obturators, prostheses were used for two to three months until healing and resorption were found satisfactory, after which the definitive obturators were fabricated. Results: The speech intelligibility test (SIT) was employed for the evaluation of the speech ability. Significant improvements were found in the mean speech intelligibility test score (SITS), from 0.02% in patients without prosthetic obturation to 94.10% in patients with immediate obturation on the second day, 95.60% in patients with immediate obturation on the 20th day, and 95.97% in patients with definitive obturation.